Perencanaan Drainase Berbasis Eco-Technology ditinjau dari Migrasi Ular (Studi Kasus: Suaka Rhino Sumatera, Taman Nasional Way Kambas) - Herison, Ahmad; Romdania, Yuda; Wahono, Endro Prasetyo; Fahri, Muhammad Yusrizal (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2020)
ABSTRACTWay Kambas National Park (TNWK) is one of the conservation areas in Lampung Province. The National Park functions to protect, preserve various kinds of animals and conservation. Design based on Eco-Technology is an absolute requirement for the sustainability of the region. This study aims to plan Eco-Technology-based drainage from road construction in the Sumatra Rhino Sanctuary (SRS), Way Kambas National Park, with snake objects. Every infrastructure development, such as drainage, must pay attention to the lives of wild animals such as snakes. Planning starts with calculating hydrological analysis to produce a debit plan with a rational method. Analysis of snake migration is done to determine the behavior and migration of snakes. Based on the calculation results there is no flood point from the planning of cross-section D1-D8 with the width of the channel width (b) = 20 cm, water depth (h) = 14.47 cm, peak width (B) = 220 cm, cross-section = 10Ã‚Â°Ã‚Â and cross-section material used is soil. With the drainage concept, the migration of snakes from one span to another is not disturbed to maintain the balance of the natural ecosystem. The conclusion is that the drainage design obtained is getting sloping, so the drainage conditions are better and friendly to snakes.Keywords: Eco-Technology, drainage, conservation, Way Kambas National Park, snake migrationABSTRAKTaman Nasional Way Kambas (TNWK) merupakan satu diantara kawasan konservasi yang berada di Provinsi Lampung. Taman Nasional berfungsi untuk melindungi, melestarikan berbagai macam satwa dan konservasi. Desain yang berbasis Eco-TechnologyÃ‚Â merupakan syarat mutlak untuk keberlanjutan kawasan itu.Ã‚Â Penelitian ini bertujuan untuk merencanakan drainase berbasis Eco-Technology dari suatu pembangunan jalan di Suaka RhinoÃ‚Â Sumatera (SRS), Taman Nasional Way Kambas dengan objek ular. Setiap pembangunan Infrastruktur seperti drainase harus memperhatikan kehidupan satwa liar seperti ular. Perencanaan dimulai dengan melakukan perhitungan analisis hidrologi untuk dapat menghasilkan debit rencana dengan metode rasional. Analisis migrasi ular dilakukan untuk mengetahui perilaku dan migrasi ular. Berdasarkan hasil perhitungan tidak terdapat titik banjir dari perencanaan penampang D1-D8 dengan ukuran lebar dasar saluran (b) = 20 cm, kedalaman air (h) = 14,47 cm, lebar puncak (B) = 220 cm, kemiringan penampang = 10Ã‚Â°Ã‚Â dan bahan penampang yang digunakan adalah tanah. Dengan adanya konsep drainase tersebut, migrasi ular dari bentang satu ke bentang lainnya tidak terganggu sehingga dapat menjaga keseimbangan ekosistem alam. Kesimpulannya adalah desain drainase yang didapat makin landai, maka kondisi drainase makin baik dan ramah terhadap ular.Kata kunci:Ã‚Â Eco-Technology, drainase, konservasi, Taman Nasional Way Kambas, migrasi ular